2021
DOI: 10.1038/s41598-021-00251-4
|View full text |Cite
|
Sign up to set email alerts
|

The early maternal environment shapes the parental response to offspring UV ornamentation

Abstract: Parents allocate resources to offspring to increase their survival and to maximize their own fitness, while this investment implies costs to their condition and future reproduction. Parents are hence expected to optimally allocate their resources. They should invest equally in all their offspring under good conditions, but when parental capacity is limited, parents should invest in the offspring with the highest probability of survival. Such parental favouritism is facilitated by the fact that offspring have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Had these previous studies aimed at reducing total brightness (and not only UV chroma), they would have likely found stronger effects in intra‐family interactions. Indeed, given the large within‐nest effect of body mass on juvenile brightness, parents could rely on this trait to adjust their feeding strategies within their brood (García‐Campa et al, 2021 ; Mas & Kölliker, 2011 ; Morales & Velando, 2018 ). Therefore, total brightness could have evolved as a condition‐dependent trait to signal nestling quality to other family members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Had these previous studies aimed at reducing total brightness (and not only UV chroma), they would have likely found stronger effects in intra‐family interactions. Indeed, given the large within‐nest effect of body mass on juvenile brightness, parents could rely on this trait to adjust their feeding strategies within their brood (García‐Campa et al, 2021 ; Mas & Kölliker, 2011 ; Morales & Velando, 2018 ). Therefore, total brightness could have evolved as a condition‐dependent trait to signal nestling quality to other family members.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, at the intra-brood level, family members might not use UV chroma as a reliable signal of body mass. This was unexpected since we have experimentally demonstrated in the study population that chicks with reduced UV chroma gain less body mass (Morales & Velando, 2018) and that this trait is used as a signal during intra-family interactions (García-Antón et al, In press;García-Campa et al, 2021;Morales & Velando, 2018). Moreover, cavity-nesting passerines are especially good at detecting changes in UV reflectance (Avilés et al, 2006;Hunt et al, 2003;Wiebe & Slagsvold, 2009), which points to UV chroma as a promising candidate for a signal inside cavities.…”
Section: Condition Dependence: Nestling Color As An Honest Signal Of ...mentioning
confidence: 93%
See 1 more Smart Citation
“…However, in line with previous research, we found the presence of sexual dichromatism (both chroma and brightness) in blue tit nestling plumage (e.g., Jacot & Kempenaers, 2007) and lack thereof in great tits (Isaksson et al, 2008), suggesting a possible difference in the signalling role of this trait between species. Although still under debate, growing evidence points to a signalling function of nestling colouration in the blue tit (García-Campa et al, 2021; Morales & Velando, 2018), while in the great tit there is no evidence of parental preference towards more coloured nestlings (Tschirren et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, all studies on colouration of hole-nesters come from populations breeding in nestboxes or from birds kept in aviaries, which represents a significant knowledge gap. Despite the fact that the biological meaning of juvenile colouration is still debated, there are indications of its role in parent-offspring communication in both nesting and post-fledging period, informing adults on offspring quality and thus modulating parental provisioning effort (Tanner & Richner, 2008; Galván et al, 2008; Tschirren et al, 2003; Morales & Velando, 2018; García-Campa et al, 2021). Otherwise, it may play a role in establishing social hierarchies between juveniles, act as anti-predatory camouflage in bright deciduous forest (Slagsvold & Lifjeld, 1985; Tschirren et al, 2003), or be the by-product the expression of a genetic correlation with adult colouration (Drobniak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%